2000
DOI: 10.1063/1.481271
|View full text |Cite
|
Sign up to set email alerts
|

A study of the BrO and BrO2 radicals with vacuum ultraviolet photoelectron spectroscopy

Abstract: The BrO radical, prepared by the BrϩO 3 reaction, has been investigated by ultraviolet photoelectron spectroscopy. Two vibrationally resolved bands were observed corresponding to the ionizations BrO ϩ (X 3 ⌺ Ϫ )←BrO(X 2 ⌸) and BrO ϩ (a 1 ⌬)←BrO(X 2 ⌸). These assignments are supported by the results of complete active space self-consistent field/multireference configuration interaction ͑CASSCF/MRCI͒ calculations performed as part of this work. The adiabatic ionization energies of these bands were measured as (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
17
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 41 publications
7
17
0
Order By: Relevance
“…Ab initio studies on the reaction mechanism of Cl+O 3 →ClO+O 2 8 and F+O 3 →FO+O 2 9 have already been performed. The Br+O 3 reaction has been investigated by ultraviolet photoelectron spectroscopy, and the Br+O 3 reaction is exothermic by 32.3 kcal/mol 10. The rate constant of this reaction at 298 K is (1.2 ± 0.2) × 10 −12 cm 3 mol −1 s −1 11.…”
Section: Introductionmentioning
confidence: 99%
“…Ab initio studies on the reaction mechanism of Cl+O 3 →ClO+O 2 8 and F+O 3 →FO+O 2 9 have already been performed. The Br+O 3 reaction has been investigated by ultraviolet photoelectron spectroscopy, and the Br+O 3 reaction is exothermic by 32.3 kcal/mol 10. The rate constant of this reaction at 298 K is (1.2 ± 0.2) × 10 −12 cm 3 mol −1 s −1 11.…”
Section: Introductionmentioning
confidence: 99%
“…By studying the Br + O3 reaction at short reaction times, using efficient pumping and electron detection methods, it proved possible to obtain sufficient concentrations of BrO to use PES to study its electronic structure and determine ionization energies to its low-lying ionic states. Also from the vibrationally resolved photoelectron bands, spectroscopic constants (equilibrium bond lengths, re, and vibrational constants ωe and ωexe ) were obtained for the ionic states (4).…”
Section: Br + 3o2mentioning
confidence: 99%
“…With quantum chemical computing programs being readily available, geometries and normal modes of small to medium size molecules in different electronic states can now be calculated routinely. Based on these methods, numerous applications of FC calculations have been presented in the literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14], and most of these studies just focus on the interpretation of experimentally known spectra. Because the geometry difference between two electronic states is a major factor that influences FC intensities, the simulation of vibronic spectra of ployatomic molecules can be regarded as a valuable test with respect to the quality of calculated geometries and as a starting point to obtain improved structures.…”
Section: Introductionmentioning
confidence: 99%
“…Because the geometry difference between two electronic states is a major factor that influences FC intensities, the simulation of vibronic spectra of ployatomic molecules can be regarded as a valuable test with respect to the quality of calculated geometries and as a starting point to obtain improved structures. In addition, spectral simulations of vibrational structure based on computed Franck-Condon factors (FCF) could provide fingerprint type identification of an observed spectrum, in terms of both the carrier and the electronic states in the transition (see, for examples, [9,10], and references therein). Also, it has been demonstrated that spectral simulations can be very useful in establishing vibrational assignments in an electronic spectrum observed with complex vibrational structure [1][2][3][4][5]7,10,11].…”
Section: Introductionmentioning
confidence: 99%